IDENTIFIKASI CURAH HUJAN EKSTREM DI KOTA SEMARANG MENGGUNAKAN ESTIMASI PARAMETER MOMEN PROBABILITAS TERBOBOTI PADA NILAI EKSTREM TERAMPAT (Studi Kasus Data Curah Hujan Dasarian Kota Semarang Tahun 1990-2013) - Annisa Rahmawati; Agus Rusgiyono; Triastuti Wuryandari (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
The methods used to analyze extreme rainfall is the Extreme Value Theory (EVT). One of the approaches of EVT is the Block Maxima (BM) which follows the distribution of Generalized Extreme Value (GEV). In this study, the dasarian rainfall data of 1990-2013 in the Semarang City is divided based on block monthly and the month examined are October, November, December, January, February, March and April. The resulted blocks are 24 with 3 observations each block. Estimated parameter of form, location and scale are obtained by using the method of Probability Weight Moments (PWM). The result of this study is January has the greatest occurrence chance of extreme value with the value of estimated parameter of form 0,3840564, location 138,8152989 and scale 68,6067117. In addition, the alleged maximum value of dasarian rainfall obtained in a period of 2, 3, 4, 5 and 6 years are 243,45753 mm, 308,23559 mm, 357,26996 mm, 397,96557 mm and 433,28889 mm. Keywords: rainfall, Extreme Value Theory, Block Maxima, Generalized Extreme Value, Probability Weight Moments